Perhitungan Waktu dan Biaya Pelaksanaan Pembangunan Struktur Atas Lantai Basement dan Podium 8 Lantai pada Gedung Apartment Menggunakan Aluminium Formwork - Novia Dwi Handayani (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
This study discussed the calculation of time and cost in the construction of the upper structure of apartment building using aluminum formwork. Aluminium formwork was chosen by consideration of its advantages in implementation time, quality, and cost. The use of aluminium formwork is suitable for use on typical floors as apartment building. In addition, aluminium formwork is coherent with green building concept. Planning begins by determined construction method, then proceeds with the calculation of quantity, productivity, duration and RAP. Scheduling was carried out using PDM and Microsoft Project. Based on scheduling and work weights, S-Curve was made. The calculation results obtained duration of Aluminium Formwork implementation is 70 working days with total cost of Rp. 14,238,023,01. In contrast, using conventional method shows total cost is Rp. 13,893,023,48 and the duration is 103 working days. The use of aluminium formwork is more expensive by Rp. 1,050,531,78 and the work process is faster than conventional.